PENGGOLONGAN SAHAM BLUE CHIP BERDASARKAN KAPITALISASI PASAR PADA BURSA EFEK INDONESIA TAHUN 2017-2020 - Ida Hendarsih; Sri Harjunawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
In general, investors usually like shares that are already well-known in the market because these shares have products that have become market leaders, their shares have a high level of liquidity and market capitalization or so-called Blue Chips. In selling on the Indonesian securities bus (BEI) these shares have a high rating with a stable price compared to other share members. Blue chip stock valuation uses secondary data in the form of sales data of Blue Chip companies listed on the Indonesia Stock Exchange (IDX) and other sources in 2017-2020 with population data is the sale of 5 (five) Blue Chips shares. The selection and collection of sample data using purposive sampling. Analysis of the market capitalization of the five largest Blue Chips stock lists on the Indonesia Stock Exchange in 2017-2020 is measured by multiplying the stock market price by the number of shares outstanding. Market capitalization value data is the closing price taken from the Indonesia Stock Exchange. The higher the share price of the capital, the higher the profit for the shareholders. Banks that are always on the chip feather list based on market capitalization are Bank Central Asia, Bank Rakyat Indonesia PT. Telekomunikasi Indonesia Tbk, PT. Unilever Indonesia Tbk and Bank Madiri.